Influence of Hydrogen Enrichment Strategy on Performance Characteristics, Combustion and Emissions of a Rotary Engine for Unmanned Aerial Vehicles (UAVs) - Kucuk, Merve; Surmen, Ali; Sener, Ramazan (Mdpi, 2022)
In recent years, there has been great interest in Wankel-type rotary engines, which are one of the most suitable power sources for unmanned aerial vehicle (UAV) applications due to their high power-to-size and power-to-weight ratios. The purpose of the present study was to investigate the potential of a hydrogen enrichment strategy for the improvement of the performance and reduction of the emissions of Wankel engines. The main motivation behind this study was to make Wankel engines, which are already very advantageous for UAV applications, even more advantageous by applying the hydrogen enrichment technique. In this study, hydrogen addition was implemented in a spark-ignition rotary engine model operating at a constant engine speed of 6000 rpm. The mass fraction of hydrogen in the intake gradually increased from 0% to 10%. Simulation results revealed that addition of hydrogen to the fuel accelerated the flame propagation and increased the burning speed of the fuel, the combustion temperature and the peak pressure in the working chamber. These phenomena had a very positive effect on the performance and emissions of the Wankel engine. The indicated mean effective pressure (IMEP) increased by 8.18% and 9.68% and the indicated torque increased by 6.15% and 7.99% for the 5% and 10% hydrogen mass fraction cases, respectively, compared to those obtained with neat gasoline. In contrast, CO emissions were reduced by 33.35% and 46.21% and soot emissions by 11.92% and 20.06% for 5% and 10% hydrogen additions, respectively. NOx emissions increased with the application of the hydrogen enrichment strategy for the Wankel engine.
Keywords: CFD simulation; combustion; emission; hydrogen enrichment; Wankel engine; UAVs